2019
DOI: 10.1680/jgere.18.00021
|View full text |Cite
|
Sign up to set email alerts
|

A review of piling industry practices in Dubai, UAE: proposed UCS-based correlations

Abstract: There is limited published information available on design guidance and performance of deep pile foundations in Dubai, UAE. In response to this situation, the piling industry tends to be over-conservative when designing foundation systems for buildings and infrastructure. Consultants, pile testing experts and the Dubai Creative Clusters Authority decided to collaborate with a common goal: share information with the industry and make pile design recommendations to help colleagues prevent the large-scale over-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The rock is weak to very weak with average UCS values in the range of 1 to 3 MPa. An average UCS pro le from another similar study reported byLatapie & Lochaden (2016) andLatapie et al (2018) for the same area also supports the conclusion that the vast majority of UCS values are in a similar range, 1.5 to 3 MPa, to that shown in Figs.7a and 7b.5 Load Cell Test Data And Back AnalysisOnly skin friction measurements from load cell test data have been used in this study. The load cell and corresponding ground parameter data have been collected from load test and foundation contractors as well as from the Dubai creative cluster authority for research purposes, and the project names are therefore con dential.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The rock is weak to very weak with average UCS values in the range of 1 to 3 MPa. An average UCS pro le from another similar study reported byLatapie & Lochaden (2016) andLatapie et al (2018) for the same area also supports the conclusion that the vast majority of UCS values are in a similar range, 1.5 to 3 MPa, to that shown in Figs.7a and 7b.5 Load Cell Test Data And Back AnalysisOnly skin friction measurements from load cell test data have been used in this study. The load cell and corresponding ground parameter data have been collected from load test and foundation contractors as well as from the Dubai creative cluster authority for research purposes, and the project names are therefore con dential.…”
supporting
confidence: 79%
“…Kulhawy et al (2005) reviewed these methods to predict rock socket friction (f s ) and highlighted a relative lack of sophistication in earlier empirical methods and also commented that in the load test-based methods, the UCS of rock used in developing these correlations was not the average UCS over test depth and might not represent the values at the test locations. Furthermore, many of these methods were developed mainly for small diameter shallow piles with low capacities in speci c geological conditions (Williams and Pells, 1999, Alrifai, 2007, Ibrahim et al, 2009, Latapie et al, 2018, Manoj et al, 2020. There is also a variation in the correlation coe cient α of 0.15 to 0.80 between the lower and upper bound relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this project, the intact modulus is assumed as 400q uc which is still lower than what can be obtained from pressure meter tests or suggested by others, cf. Latapie et al (2019), but for the author it gives reliable results for highly loaded piles. In the above suggestions, the modulus is assumed as the secant modulus of deformation at a factor of safety of around 2.0, i.e., at a stress level of about half of the unconfined strength.…”
Section: Ground Layers and Their Propertiesmentioning
confidence: 95%
“…The resulting ultimate skin resistance corresponding to each layer is shown in the table. There are many methods to estimate the skin resistance of bored piles socketed in weak rocks but a recent study on the rocks of Dubai, Latapie et al (2019), suggested that f sult may be taken equal to 0.42√q uc (in MPa). Still, the author feels that relating the skin resistance to RQD is more reliable although the values obtained from Williams and Pells method are more conserva tive than the latter suggestion.…”
Section: Ground Layers and Their Propertiesmentioning
confidence: 99%